Correction: Mazumder et al. Combined Heart-Liver Transplant vs. Heart Transplant Alone: A Single Center Experience. Transplantology 2024, 5, 186–192 - Ritika Mazumder; Andrew Ford; Omar T. Sims; Jamak Modaresi Esfeh (Transplantology)
In the original publication [...]